Clevidipine-Induced Extreme Hypoxemia in a Neurosurgical Patient: A Case Report. Issue 2 (15th January 2020) - Short, Jack H.; Fatemi, Parastou; Ruoss, Stephen; Angelotti, Timothy
Abstract : Clevidipine-induced pulmonary shunting is a little-reported adverse effect, manifesting as refractory hypoxemia, which may cause significant patient harm. We present the case of a mechanically ventilated patient admitted to the intensive care unit following a neurosurgical procedure. He was treated postoperatively with clevidipine for blood pressure management, and within 16 hours, he developed profound refractory hypoxemia, requiring increased ventilatory support. A workup for other causes was negative. The hypoxemia recovered within 1 hour of clevidipine discontinuation. Though other calcium channel blockers have been reported to cause pulmonary shunting from vasodilation, this is a novel case report for clevidipine-induced hypoxemia.